Perundungan Dunia Maya (cyberbullying) dan Cara Mengatasi Perspektif Islam - Anisah, Ani; Nazib, Fiqra; Putri, Cut Mutiara (Universitas Garut, 2024)
The aim of writing this article is to provide a comprehensive view of the problem of bullying in the digital era, to mobilize empathy and awareness, as well as inspire positive action and change people's perceptions of unethical online behavior, thereby creating a safer and friendlier online world. This research was researched using library research methods. From the results of this research, it can be understood that bullying is an act of harassment, both emotional and physical, carried out by someone, especially a child, intentionally to hurt another individual. Cyberspace refers to digital or virtual space where humans interact and carry out activities via the internet network. In cyberspace, people can communicate and carry out various activities through various online platforms such as websites, social media, discussion forums and various other applications. Cyberbullying or bullying in the virtual world, refers to acts of harassment, intimidation, or humiliation that occur online via various internet platforms such as social media, text messages, or other forms of digital communication. Islam teaches compassion, justice and empathy towards others. Cyberbullying goes against these values because it can cause emotional suffering to the victim. Islam encourages its followers to support each other and understand the suffering of others.